Report of 7 cases of congenital amputations due to amniotic bands (Colombia Medica, 1992)
Seven cases of disruptive pathology due to amniotic bands are described, illustrating the wide variability of anomalies that can be derived. Most accepted theories of pathogenesis are reviewed to explain the origin of this type of congenital pathology. Probable risk factors are analyzed, and the need for strict prenatal control when they are present is noted.